Transformation of Media Narratives About Ukraine’s Euro-Atlantic Integration - Сащук, Ганна Миколаївна; Товмаш, Дмитро Анатолійович (Київський національний університет імені Тараса Шевченка, 2025)
The article presents a comprehensive analysis of the transformation of media narratives about Ukraine’s Euro-Atlantic integration within the time span of 2000–2025. It demonstrates that the evolution of media discourse around NATO reflects profound changes in Ukraine’s system of political culture, information policy, and social identity. The study reveals how communicative emphases in Ukrainian media have shifted – from the geopolitical rhetoric of a “choice between East and West” to the concepts of “collective security” and “information sovereignty.” It is shown that after 2014, security journalism became a central factor in shaping narratives about NATO as a guarantor of peace, and after 2022 – as a partner in the joint resistance to hybrid aggression. The study proves that Ukrainian media perform not only the function of retransmission but also the construction of national identity, within which Euro-Atlantic integration is perceived as a strategy of political self-affirmation. An interdisciplinary approach (institutional, content, discourse, and comparative analysis) was applied, allowing to generalize the regularities of the transformation of communicative frameworks – from political rhetoric to the cultural and value-oriented discourse of collective security. Based on the conducted analysis, the main problems of modern media narratives were identified: regional disparities in their dissemination, excessive officialization of state messages, lack of stable coordination between state and independent media, insufficient use of digital platforms, and the imperfection of communication effectiveness assessment systems. The directions for improvement are proposed: establishing network-based interaction between journalists and government communicators, developing narrative journalism, creating a system for narrative monitoring, and introducing Euro-Atlantic modules into journalism education programs. It is summarized that the transformation of media narratives about Euro-Atlantic integration is not only a process of adapting the information space to NATO standards but also an element of the democratic modernization of Ukrainian society that strengthens its agency, European identity, and resilience in confronting hybrid threats.

У статті здійснено комплексний аналіз трансформації медіана ративів про євроатлантичну інтеграцію України у часовому діапазоні 2000 — 2025 рр. Показано, що розвиток медійного дискурсу навколо НАТО є відображенням глибинних змін у системі політичної культури, інформа ційної політики та суспільної ідентичності України. З’ясовано, як змінюва лися комунікативні акценти в українських медіа — від геополітичної рито рики «вибору між Сходом і Заходом» до концепції «спільної безпеки» та «інформаційного суверенітету». Показано, що після 2014 р. журналістика безпеки стала центральним чинником формування наративів про НАТО як гаранта миру, а після 2022 р. — як партнера у спільному протистоянні гібридній агресії. У роботі доведено, що українські медіа виконують функцію не лише ретрансляції, а й конструювання національної ідентичності, у межах якої євроатлантична інтеграція сприймається як стратегія політичного само ствердження. Застосовано міждисциплінарний підхід (інституційний, контент-, дискурс- і порівняльний аналіз), що дозволив узагальнити за кономірності зміни комунікативних рамок — від політичної риторики до культурно-ціннісного дискурсу спільної безпеки. На основі проведеного аналізу виокремлено основні проблеми су часних медіанаративів: регіональна нерівномірність їх поширення, над мірна офіціалізація державних меседжів, відсутність сталої координації між державними та незалежними ЗМІ, недостатнє використання цифро вих платформ і недосконалість системи оцінювання ефективності кому нікацій. Запропоновано напрями вдосконалення: формування мережевої взаємодії журналістів і державних комунікаторів, розвиток наративної журналістики, створення системи моніторингу наративів, запровадження євроатлантичних модулів у програми журналістської освіти. Узагальнено, що трансформація медіанаративів про євроатлантич ну інтеграцію є не лише процесом адаптації інформаційного простору до стандартів НАТО, а й елементом демократичної модернізації українсько го суспільства, який зміцнює його суб’єктність, європейську ідентичність і стійкість у протистоянні гібридним загрозам.
Трансформація медіанаративів про євроатлантичну інтеграцію України
Keywords: медіанаратив; стратегічні комунікації; політичні комунікації; євроінтеграція; інформаційна політика; інформаційна безпе ка; партнерство; Україна; НАТО; media narrative; strategic communications; political communications; European integration; information policy; information security; partnership; Ukraine; NATO